Towards Autonomous Robotic Systems 17th Annual Conference, TAROS 2016, Sheffield, UK, June 26--July 1, 2016, Proceedings - Alboul, Lyuba; Damian, Dana; Aitken, Jonathan M. (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the refereed proceedings of the 17th Annual Conference on Towards Autonomous Robotics, TAROS 2016, held in Sheffield UK, in June/July 2016. The 23 revised full papers presented together with 15 short papers were carefully reviewed and selected from 56 submissions. The overall program covers various aspects of robotics, including navigation, planning, sensing and perception, flying and swarm robots, ethics, humanoid robotics, human-robot interaction, and social robotics.